Dy adsorption and penetration on defected graphene by first-principles calculations. (15th February 2018) - Yu, Liwei; Du, Chunyan; Liu, Xiaojie
Abstract: Dy adatom adsorption and penetration on defected graphene were studied using first-principles calculations. We show that adsorption of Dy adatom on defect is energetically more favorable than on pristine graphene. Strong covalent bonding between Dy and C atoms at the defect sites is confirmed by interaction charge density analysis. We also found that the pathways for Dy penetration through defects with 1 and 2 missing carbon atoms are different from those through larger holes in graphene due to strong spatial confinement effects. The larger size of the hole is, the smaller barrier for Dy penetration.